Analisis Yuridis Ketentuan-Ketentuan Pemrosesan Data Pribadi Berdasarkan Persetujuan Pada Aplikasi Identitas Kependudukan Digital (RechtJiva, 2025)
This study analyzes the disclaimer of liability by personal data controllers and the processing of personal data based on consent within the Digital Population Identity (IKD) application, in light of privacy policies and Indonesian regulations. The research theme stems from the disharmony between the Ministry of Home Affairs Regulation No. 72 of 2022 and Law No. 27 of 2022 on Personal Data Protection (PDP Law). The inclusion of liability disclaimer clauses by data controllers also motivates this study. Using a normative juridical method, it employs statutory, conceptual, and comparative approaches. Legal materials collected through literature reviews are analyzed using grammatical, systematic, and comparative legal interpretation. The findings reveal that crucial information regarding data processing based on consent is often omitted or inconsistent with Article 21(1) of the PDP Law. Additionally, the liability disclaimer clause weakens personal data protection. Therefore, it is necessary to revise the Ministry of Home Affairs Regulation No. 72 of 2022 to clarify data processing purposes, data types and relevance, retention periods, data subject rights, as well as enhancing data security and digital service interoperability, as implemented in the Besluit Digitale Overheid in the Netherlands.